Surfactant toxicity in a case of (4-chloro-2-methylphenoxy) acetic acid herbicide intoxication. (August 2015) - Hwang, I; Lee, JW; Kim, JS; Gil, HW; Song, HY; Hong, SY
Objective: Self-poisoning with (4-chloro-2-methylphenoxy) acetic acid (MCPA) is a common reason for presentation to hospitals, especially in some Asian countries. We encountered a case of a 76-year-old woman who experienced unconsciousness, shock and respiratory failure after ingesting 100 mL MCPA herbicide. We determined whether the surfactant in the formulation was the chemical responsible for the toxic symptom in this patient. Design: 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) cell viability and lactate dehydrogenase (LDH) cytotoxicity assays were performed on human brain neuroblastoma SK-N-SH cells. The expressions of 84 genes in 9 categories that are implicated in cellular damage pathways were quantified using an RT 2 Profiler™ PCR array on a human neuronal cell line challenged with polyoxyethylene tridecyl ether (PTE). Setting: Pesticide intoxication institute in university hospital. Interventions: Extracorporeal elimination with intravenous lipid emulsion. Measurements: Cell viability and gene expression. Main Results: In the MTT assay, MCPA only minimally decreased cell viability even at concentrations as high as 1 mM. Cells treated with 1-methoxy-2-propanol, dimethylamine and polypropylene glycol exhibited minimal decreases in viability, whilst the viability of cells challenged with PTE decreased dramatically; only 15.5% of cells survived after exposure to 1 µM PTE. Similarly, the results of the LDH cytotoxicity assay showed that MCPA had very low cytotoxicity, whilst cells treated with PTE showed incomparably higher LDH levels ( p < 0.0001). PTE up-regulated the expressions of genes implicated in various cell damage pathways, particularly genes involved in the inflammatory pathway. Conclusions: The surfactant PTE was likely the chemical responsible for the toxic symptom in our patient.